Genetic control of sex-dependent meiotic recombination in the major histocompatibility complex of the mouse. - Shiroishi, T (1991)
Meiotic recombination within the proximal region of the major histocompatibility complex (MHC) of the mouse is not random but occurs in clusters at certain restricted sites, so-called recombinational hotspots. The wm7 haplotype of the MHC, derived from the wild mouse, enhances recombination specifically during female meiosis within a fragment of 1.3 kb of DNA located between the A beta 3 and A beta 2 genes in genetic crosses with laboratory haplotypes. Previous studies revealed no significant strain differences in nucleotide sequences around the hotspot, irrespective of the ability of the strain to enhance the recombination. It appeared that a distant genetic element might, therefore, control the rate of recombination. In the present study, original recombinants whose breakpoints were defined by direct sequencing of PCR-amplified DNAs were tested for the rate of secondary recombination in the crosses with laboratory strains in order to determine the location of such a genetic element. The results clearly demonstrated that the chromosomal segment proximal to the hotspot is essential for enhancement of recombination. Moreover, the male recombination is suppressed by a segment distal to the hotspot.